Identification and characterization of cytochrome P450 1232A24 and 1232F1 from Arthrobacter sp. and their role in the metabolic pathway of papaverine. (13th February 2019) - Klenk, Jan M; Fischer, Max-Philipp; Dubiel, Paulina; Sharma, Mahima; Rowlinson, Benjamin; Grogan, Gideon; Hauer, Bernhard
Abstract: Cytochrome P450 monooxygenases (P450s) play crucial roles in the cell metabolism and provide an unsurpassed diversity of catalysed reactions. Here, we report the identification and biochemical characterization of two P450s from Arthrobacter sp., a Gram-positive organism known to degrade the opium alkaloid papaverine. Combining phylogenetic and genomic analysis suggested physiological roles for P450s in metabolism and revealed potential gene clusters with redox partners facilitating the reconstitution of the P450 activities in vitro . CYP1232F1 catalyses the para demethylation of 3, 4-dimethoxyphenylacetic acid to homovanillic acid while CYP1232A24 continues demethylation to 3, 4-dihydroxyphenylacetic acid. Interestingly, the latter enzyme is also able to perform both demethylation steps with preference for the meta position. The crystal structure of CYP1232A24, which shares only 29% identity to previous published structures of P450s helped to rationalize the preferred demethylation specificity for the meta position and also the broader substrate specificity profile. In addition to the detailed characterization of the two P450s using their physiological redox partners, we report the construction of a highly active whole-cell Escherichia coli biocatalyst expressing CYP1232A24, which formed up to 1.77 g l −1 3, 4-dihydroxyphenylacetic acid. Our results revealed the P450s' role in the metabolic pathway of papaverine enabling further investigation and application of these biocatalysts.